2018
DOI: 10.1002/hed.25351
|View full text |Cite
|
Sign up to set email alerts
|

Combination of serum squamous cell carcinoma antigens 1 and 2 as potential diagnostic marker for sinonasal squamous cell carcinoma and inverted papilloma

Abstract: Background Differentiating inverted papilloma from squamous cell carcinoma (SCC) is sometimes difficult. We evaluated the clinical usefulness of serum SCCA1 and SCCA2 in the management of patients with inverted papilloma or SCC. Methods Serum and tissue samples for the analysis of SCCA1, SCCA2, and SCC antigen were taken from 18 patients with sinonasal inverted papilloma and 23 cases with sinonasal SCC. The SCCA1, SCCA2, and SCC antigen levels were determined. Results The serum SCCA1 concentration was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…While SCCA is produced by two homologous genes, SCCA-1 and SCCA-2, SCCA-1 plays a pivotal role in the diagnosis of IP, with SCCA-2 providing limited diagnostic utility. Previous analysis of SCCA-2 in CRS, IP, and sinonasal SCC demonstrated that SCCA-2 levels are significantly higher in sinonasal SCC than in CRS and IP when measured using different in-house assay systems [27]. Our results for SCCA-2 levels in IP and CRS were consistent with that report [27].…”
Section: Discussionsupporting
confidence: 90%
“…While SCCA is produced by two homologous genes, SCCA-1 and SCCA-2, SCCA-1 plays a pivotal role in the diagnosis of IP, with SCCA-2 providing limited diagnostic utility. Previous analysis of SCCA-2 in CRS, IP, and sinonasal SCC demonstrated that SCCA-2 levels are significantly higher in sinonasal SCC than in CRS and IP when measured using different in-house assay systems [27]. Our results for SCCA-2 levels in IP and CRS were consistent with that report [27].…”
Section: Discussionsupporting
confidence: 90%
“…Yasumatsu et al [29] reported that SCCA1 was more strongly expressed in SIP tissues than in SCC tissues and, conversely. On the contrary, SCCA2 was predominantly expressed in SCC tissues.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the Yasumatsu study are consistent with these previous studies of cervical cancer that found SCCA2 levels were more strongly expressed in malignant cervical tissues than in normal tissues. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Yasumatsu et al reported that SCCA1 was more strongly expressed in SIP tissues than in SCC tissues. 30 In contrast, SCCA2 was predominantly expressed in SCC tissues. The results of the Yasumatsu study are consistent with these previous studies of cervical cancer that found SCCA2 levels were more strongly expressed in malignant cervical tissues than in normal tissues.…”
mentioning
confidence: 95%
See 1 more Smart Citation